Preface - Said-Hung, Elías Manuel; Montero Díaz, Julio (IGI Global, 2024)
Expressions of hate are words or actions that are discriminatory, hostile, or violent to a person or group for racial, sexual, ideological, ethnic, or identity reasons. Such expressions contribute to an environment of prejudice and intolerance towards those who are targeted. The spread of hate speech has been exacerbated by the growth of social media networks, and dissemination strategies (e.g., astroturfing) are becoming increasingly complex. Although there has been an exponential increase in the study of hate speech in recent years, most methods have focused on the English language, limiting research of the phenomenon in other languages such as Spanish, Italian, and Portuguese. It is crucial to understand the role played by digital media and journalism in the dissemination, detection, and control of hate speech from current digital scenarios. News Media and Hate Speech Promotion in Mediterranean Countries provides relevant theoretical frameworks and the latest empirical research findings about hate speech studies including into prejudice and intolerance. Covering topics such as detecting hate speech, linguistic challenges, and the taxonomy of hate speech, this book is ideal for political decision makers, third-sector representatives, journalists, digital media professionals, and researchers.
Es el prefacio del libro: Said Hung, E. & Diaz, J. M. (Eds.). (2023). News Media and Hate Speech Promotion in Mediterranean Countries. IGI Global
Keywords: hate speech; digital media; mediterranean countries; Scopus